Botanical Literacy in the Last Ten Years: Insights from Scopus - H. Husamah; Tutut Indria Permana; Abdulkadir Rahardjanto (Universitas Pendidikan Mandalika, 2025)
This systematic literature review examines the evolution of botanical literacy research over the last decade, based on 32 Scopus-indexed studies. Nine research questions (RQs) explore publication trends, geographical distribution, subject areas, funding sponsors, co-occurring keywords, influencing factors, effective strategies, and emerging themes. Data collection followed the PRISMA protocol, with bibliometric analysis and VOSviewer used to explore trends, while Scopus AI facilitated thematic and content analysis. The analysis identified a sevenfold increase in publication volume from 2017 to 2024, with notable peaks in 2022 (n=7) and 2024 (n=7). These findings reflect a growing academic recognition of the crucial role plants play in tackling global environmental challenges. The United States and the United Kingdom lead in research, while Asian countries such as Indonesia remain underrepresented (less than 5% of total publications), highlighting the need for a more inclusive, global approach. The study also reveals the interdisciplinary nature of botanical literacy, encompassing environmental sciences, agriculture, social sciences, and fields like computer science and psychology. Key factors influencing botanical literacy include lack of interest, poor educational materials, and ineffective teaching methods. Effective strategies identified include inquiry-based learning and integrating botanical education into daily life. Emerging themes emphasize â€œScientific Literacy in Environmental Contextsâ€ as a recurring focus, reinforcing the relevance of botanical literacy in environmental education.